2010
DOI: 10.1158/1535-7163.mct-09-1130
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Study on the Rescue of Normal Tissue by Nicotinic Acid in High-Dose Treatment with APO866, a Specific Nicotinamide Phosphoribosyltransferase Inhibitor

Abstract: Inhibitor of nicotinamide phosphoribosyltransferase APO866 is a promising cancer drug currently in phase II clinical trials in oncology. Here, we present a strategy for increasing the therapeutic potential of APO866 through the rescue of normal tissues by coadministration of nicotinic acid (Vitamin B 3 ). We examined the toxicity profile of APO866 in B6D2F1 mice and the effect of oral administration of nicotinic acid on tissue toxicity. Nicotinic acid (50 mg/kg) protects mice from death and severe toxicity fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 31 publications
5
60
0
Order By: Relevance
“…Previous studies have indicated that NAPRT1 is required for nicotinic acid rescue (16,17). We wanted to test this observation in a larger panel of cell lines and identify additional determinants of nicotinic acid rescue across cancer cell lines from a diverse range of tissue types.…”
Section: Rescue Of Nampt Inhibitor Toxicity By Nicotinic Acid Is Due mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have indicated that NAPRT1 is required for nicotinic acid rescue (16,17). We wanted to test this observation in a larger panel of cell lines and identify additional determinants of nicotinic acid rescue across cancer cell lines from a diverse range of tissue types.…”
Section: Rescue Of Nampt Inhibitor Toxicity By Nicotinic Acid Is Due mentioning
confidence: 95%
“…1A). Addition of nicotinic acid to the media or food allows this pathway to generate sufficient levels of NAD to mitigate the cytotoxic effects of a NAMPT inhibitor in cultured cells and animal rodents (15)(16)(17) as well as in human megakaryocytes (18). Interestingly, some cancers do not express NAPRT1 (19), rendering this pathway nonfunctional.…”
Section: Introductionmentioning
confidence: 99%
“…An FK866 administration schedule (i.p. injection twice a day, 4 days on, 3 days off) was selected based on previous efficacy-tolerability studies (19). Although FK866 delayed tumor growth in all populations, only ERCC1-KO models displayed a significant difference in tumor volumes between the FK866 and vehicle groups ( Figure 5, B-D).…”
Section: Nampt Inhibition Is Exquisitely Toxic To Ercc1-ko Cells In Vmentioning
confidence: 99%
“…Our findings indicate that ERCC1-deficient tumors may respond to NAMPT inhibitors at lower doses than their ERCC1-proficient counterparts, which may enable reaching antitumor activity while avoiding excessive toxicities in selected populations thanks to a favorable therapeutic window. In addition, by analogy with the folate rescue used for high-dose methotrexate administration, whether the tolerability of these drugs might be improved by adding sequential vitamin B3 or NMN administration (14,19) might deserve clinical evaluation. Similarly, alternative schedules that use more frequent administration at lower doses might be worth exploring in order to achieve similar drug exposure and avoid peak-related, dose-limiting toxicity.…”
Section: Model For Ercc1-deficient Nsclc Sensitivity To Nampt Inhibitmentioning
confidence: 99%
“…The de novo biosynthesis of NAD þ from tryptophan mainly occurs in the liver and under certain stressed conditions (4). Therefore, the NAM salvage pathway represents the major route to NAD þ biosynthesis in the mammals (9)(10)(11). In cancer cells, NAMPT plays a crucial role in several physiological processes including energy generation, reductive biosynthesis, mitochondrial function, and the response to oxidative stress (1,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%